2012
DOI: 10.1007/s12311-012-0379-1
|View full text |Cite
|
Sign up to set email alerts
|

Macrocerebellum: Significance and Pathogenic Considerations

Abstract: Macrocerebellum is a rare finding characterized by an abnormally large cerebellum. Only few patients with a syndromal or isolated macrocerebellum have been reported so far. This article aims to categorize the magnetic resonance imaging (MRI) findings, quantitate the macrocerebellum by volumetric analysis, characterize the neurological and dysmorphic features and cognitive outcome, and report the results of genetic analyses in children with macrocerebellum. All MR images were qualitatively evaluated for infrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
1
31
1
Order By: Relevance
“…Regarding the abnormal thickening of the cerebellar GM described by Poretti et al (2), in our cohort of patients the cerebellar GM was judged to be normal and the significance of this finding remains unclear. We believe that volumetric analysis with segmentation of the different components of the CB (grey matter, WM and liquor) could be useful to clarify the contribution of the cortical thickening to the macrocerebellum.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Regarding the abnormal thickening of the cerebellar GM described by Poretti et al (2), in our cohort of patients the cerebellar GM was judged to be normal and the significance of this finding remains unclear. We believe that volumetric analysis with segmentation of the different components of the CB (grey matter, WM and liquor) could be useful to clarify the contribution of the cortical thickening to the macrocerebellum.…”
Section: Discussioncontrasting
confidence: 54%
“…Also in one of the subjects described by Poretti et al (2), the cerebral WM was reported as normal. So the presence of abnormal cerebral WM seems to be often, but not always, associated with macrocerebellum, while the presence of a certain degree of mental and motor delay is always present.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations